Preventive strategies for reducing intraoperative awareness due to errors in anesthetic drug delivery systems: a narrative review - Chen, Qisheng; Peng, Shixuan; Luo, Wenjun; Li, Shuzhai; Zhang, Zhiming (Frontiers in Pharmacology, 2025)
General anesthesia should induce unconsciousness and provide amnesia. Intraoperative awareness (IOA) is the unexpected awakening of the patient during general anesthesia, which also implies failure of anesthesia. Inadequate concentration of anesthetic drugs due to malfunction or error in the Anesthetic Drug Delivery Systems (ADDS) is a common cause of IOA. This review explores the risk factors for IOA associated with ADDS, focusing on issues in intravenous systems like infusion pump malfunctions, lack of carrier fluid, unrecognized venous access blockades, intraoperative dosing errors, and syringe swaps, as well as problems in inhalation systems such as anesthetic vaporizer malfunctions, insufficient carrier or fresh gas flow, and breathing circuit leaks. To tackle the unique challenges of ADDS in relation to IOA, the review discusses and emphasizes comprehensive 3E prevention strategies: (1) Enhancing training and education (such as check-listing of anesthetic delivery systems preoperatively, conducting effective communication, optimizing drug combinations, and avoiding intraoperative anesthetic medication errors); (2) Employing more monitoring intraoperatively (such as monitoring anesthetic concentration, monitoring depth of anesthesia, monitoring vital signs, and monitoring neuromuscular function); and (3) Encouraging incident reporting and audit practices. The future of ADDS may involve AI-assisted and AI-supervised management to further reduce the risk of IOA. However, more research is needed to eliminate IOA.